SYMBOLS AND POWER DISCOURSES IN THREE SHADOW PUPPET PERFORMANCES OF THE MURWAKALA PLAY - Latifah, Ayuk; Darmoko, Darmoko (UI Scholars Hub, 2025)
This study analyzes the symbols and discourses of power in three Purwa shadow puppet performances of the Murwakala play, styles of Surakarta, Yogyakarta, and Banyumas. The Murwakala play, centered on themes of purification and the transformation of power, contains a rich narrative for analyzing power dynamics through the interactions between characters such as Batara Kala (a form of destructive power), Batara Wisnu (a form of constructive power), and Batara Guru (a form of cosmic order). Using a qualitative approach, this research integrates Geertz's theory of cultural symbolism and Foucault's discourse of power to analyze how power is represented and negotiated in these performances. This study highlights the role of symbols, the classification of sukerta (individuals considered spiritually impure), and the performative elements of mantras, gending (musical compositions), and sinden (female vocalists) in constructing a powerful discourse. Additionally, the socio-cultural context of Javanese society, including rituals like ruwatan (cleansing ceremonies), is explored to understand its influence on the interpretation of power dynamics. The findings reveal distinct variations in power representation across the three styles. The Surakarta style emphasizes hierarchical and philosophical power structures, the Yogyakarta style showcases ritualistic negotiations of power, and the Banyumas style reflects a more egalitarian and communal approach. These differences underscore the adaptability of shadow puppetry as a living tradition that reflects and shapes socio-cultural values.